2008
DOI: 10.2298/vsp0804291v
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term preoperative physical therapy and education on early functional recovery of patients younger than 70 undergoing total hip arthroplasty

Abstract: The short-term preoperative program of education with the elements of physical therapy accelerated early functional recovery of patients (younger than 70) immediately after THA and we recommend it for routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 10 publications
0
65
1
17
Order By: Relevance
“…Therefore, we cannot state that a shorter hospital stay means fewer knowledge expectations fulfilled. Earlier studies have contradictory results; preoperative education was found to reduce length of hospital stay (Yoon et al, 2010) but also to have no effect on hospital stay (Sjöling, 2003, Vukomanovic et al, 2008. We did not study the existing patient educational routines and therefore cannot state if they are adequate or not.…”
Section: Table 4 Here 4 Discussionmentioning
confidence: 86%
“…Therefore, we cannot state that a shorter hospital stay means fewer knowledge expectations fulfilled. Earlier studies have contradictory results; preoperative education was found to reduce length of hospital stay (Yoon et al, 2010) but also to have no effect on hospital stay (Sjöling, 2003, Vukomanovic et al, 2008. We did not study the existing patient educational routines and therefore cannot state if they are adequate or not.…”
Section: Table 4 Here 4 Discussionmentioning
confidence: 86%
“…One study reported sense of uncertainty on discharge using a VAS scale. 506 Inclusion of this in the meta-analysis and excluding one study with change scores gave an average SMD of 4.15 (95% CI 1.46 to 6.84).…”
Section: Post-surgical Anxietymentioning
confidence: 99%
“…489,490,492,495,506,522,529,530 Five studies with 381 patients presented data suitable for the meta-analysis in Table 76 and Figure 39. 489,492,495,506,529 Four studies recorded anxiety using the STAI questionnaire during the hospital stay or the change from baseline and included either hip or hip and knee patients analysed together. 489,492,495,529 In a random-effects model, the MD was 2.97 (95% CI 0.64 to 5.30) in favour of reduced anxiety in the intervention group.…”
Section: Post-surgical Anxietymentioning
confidence: 99%
“…The prehabilitation studies (Swank et al, 2011;Vukomanovic et al, 2008) demonstrated improved functional mobility, including standing, walking and stair negotiation abilities preoperatively (Swank et al, 2011), 3 days post-operatively and upon discharge (Vukomanovic et al, 2008). Vukomanovic and colleagues (2008) randomised patients awaiting primary THR surgery to i) short-term, prehabilitation (education (one physiotherapist-led session) and physical therapy exercises (two physiotherapist-led sessions) including, bed transfers, standing, walking with crutches, sitting on chair, aided stair negotiation), or ii) no prehabilitation.…”
Section: Evidence Summary For Stair Negotiation As An Orthopaedic Rehmentioning
confidence: 99%
“…In addition, the specific impact of stair negotiation on the recovery of physical functions cannot be determined. Two studies using stair negotiation in a prehabilitation intervention demonstrated improved functional mobility both pre- (Swank et al, 2011) and post-operatively (Vukomanovic et al, 2008), when compared to standard care. No intervention used stair negotiation as i) a major component of, or ii) the sole exercise, in post-operative rehabilitation.…”
Section: Summary Of Principal Findingsmentioning
confidence: 99%